1986
DOI: 10.1111/j.1439-0434.1986.tb00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Acetobacter liquefaciens as Causal Agent of Pink‐Disease of Pineapple Fruit

Abstract: Two bacterial strains causing pink‐disease of pineapple were identified as Acetobacter liquefaciens and compared with 8 other Acetobacter liquefaciens, 10 Gluconobacter oxydans and 7 Frateuria aurantia strains. The similarieties and differences between these bacteria are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The results of Pearson correlation between bacteria and fungi showed that Komagataeibacter was highly correlated with pathogenic fungi Rosellinia and Trichothecium , suggesting that there might be functional synergy between them. Acetobacter has a strong oxidative capacity, which can cause the decay of fruits and vegetables, as well as the deterioration of wine and fruit juices [ 43 ]. Large amounts of Acetobacter were determined in rotten fruit, indicating the important role it played during the storage of ‘Huangguan’ pear.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Pearson correlation between bacteria and fungi showed that Komagataeibacter was highly correlated with pathogenic fungi Rosellinia and Trichothecium , suggesting that there might be functional synergy between them. Acetobacter has a strong oxidative capacity, which can cause the decay of fruits and vegetables, as well as the deterioration of wine and fruit juices [ 43 ]. Large amounts of Acetobacter were determined in rotten fruit, indicating the important role it played during the storage of ‘Huangguan’ pear.…”
Section: Discussionmentioning
confidence: 99%
“…It was originally described from Hawaii (Lyon 1915). Losses due to the disease were reported from Hawaii (Rohrabach and Pfeiffer 1976;Gossele and Swings 1986), the Philippines (Kontaxis and Hayward 1978), and several other countries. The disease so far has not been reported from India.…”
Section: Pink Diseasementioning
confidence: 99%
“…It has been suggested that this disease is caused by microorganisms of the families Acetobacteraceae and Enterobacteriaceae (BuDDeNhageN;DuLL,1967;gOSSeLe;SwIN gS, 1986;KONtaxIS;haywaRD, 1978;PFeIFFeR, 1976). Almost four decades ago, an isolate obtained from a diseased fruit, did not show perceptible symptoms when it was inoculated in fresh fruits but induced discoloration after heating the inoculated fruits (Rohrbach and Pfeiffer 1976).…”
Section: Causative Agents Of Pink Diseasementioning
confidence: 99%